An Empirical Model of Perceived Value and Customer Satisfaction in Mobile Phone Market: An Empirical Investigation of the Mobile Phone Industry - Al Refai, Abdalla Nayef; Mohd Noor, Nor Azila (UUM Press, 2014)
The purpose of this study is to study the relationship between perceived value and customer satisfaction in mobile phone market. In doing this, SPSS was employed as an approach to describe and analyze data while smart (PLS) was used to examine the relationship between perceived value and customer satisfaction. The researchers collected data for this study from Malaysian Mobile Phone subscribers. Out of 112questionnaires that were distributed, only 103 were returned. This study confirmed the impact of perceived value on customer satisfaction of mobile phone users in Malaysia in conformity with the findings of previous researchers especially the resource-based view that regards the customer satisfaction as a competitive advantage source and long-term success for the organization. Finally, the last part of the paper discusses the findings and makes recommendations for the future researchers.